2001
DOI: 10.1097/00004424-200112000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Relative Glycosaminoglycan Distribution in Patients with Autologous Chondrocyte Transplants

Abstract: The GAG level in grafts that were implanted for less than 12 months appeared to be lower than that in the remote cartilage. At 12 months or greater, the grafts in this study had GAG levels that were comparable to both the adjacent and remote cartilage. This preliminary study of ACT implants has shown that it is feasible to apply the dGEMRIC technique in patients with ACT as a way to obtain information related to the composition of grafts. These results provide motivation and the pilot data with which to design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
1
1

Year Published

2003
2003
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 27 publications
6
77
1
1
Order By: Relevance
“…In addition, it has recently been reported that such a correlation also exists in autologous chondrocyte transplants in humans (27). Our data show that the FCD as determined in this manner correlates not only with biochemical composition but also with biomechanical properties.…”
Section: ϫsupporting
confidence: 78%
“…In addition, it has recently been reported that such a correlation also exists in autologous chondrocyte transplants in humans (27). Our data show that the FCD as determined in this manner correlates not only with biochemical composition but also with biomechanical properties.…”
Section: ϫsupporting
confidence: 78%
“…The delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) has been shown to predict the PG content of cartilage (Bashir et al, 1999, whereas the T2 relaxation time reflects the integrity and arrangement of the collagen fibril network (Nieminen et al, 2000;Nieminen et al, 2001;Xia et al, 2001) as well as collagen and water content (Fragonas et al, 1998;Shapiro et al, 2001). Both techniques have been applied for in vivo analysis of human cartilage using clinical MR scanners (Gold et al, 2006), and e.g. cartilage maturation after repair operation has been successfully monitored (Gillis et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques have been applied for in vivo analysis of human cartilage using clinical MR scanners (Gold et al, 2006), and e.g. cartilage maturation after repair operation has been successfully monitored (Gillis et al, 2001). Acoustic properties of cartilage, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…12) (76,77). Increases in the dGEMRIC index have also been observed clinically in cartilage implants (78)(79)(80) and in the cartilage in several case studies of patients recovering from surgery and taking nutritional supplements (81).…”
Section: Should Mri Be Used To Determine Entry Criteria For Clinical mentioning
confidence: 73%